Ticket to Hollywood a novel - Reilly, Gary (Denver Running Meter Press, 2013)
"Meet Denverite Brendan Murphy-- or "Murph" as he's know to the rest of the world. That world consists mostly of fares and doormen and fellow hacks from the Rocky Mountain Taxicab Company... Come prowl the mean streets of Denver with Murph and ponder the meaning of the world and all sorts of deep questions, such as "Why would anyone want to DO anything?"--P. [4] of cover.
114471
Keywords: Taxicab drivers -- Fiction; Colorado -- Denver; Fiction; Romans